A Systematic Review of the Effects of Arbuscular Mycorrhizal Fungi on Root-Lesion Nematodes, Pratylenchus spp. - Gough, Elaine C.; Owen, Kirsty J.; Zwart, Rebecca S.; Thompson, John P. (Frontiers in Plant Science, 2020)
Root-lesion nematodes Pratylenchus spp. and arbuscular mycorrhizal fungi (AMF) occupy the same ecological niche in the phytobiome of many agriculturally important crops. Arbuscular mycorrhizal fungi can enhance the resistance or tolerance of a plant to Pratylenchus and previous studies have been undertaken to investigate the relationship between these organisms. A restructuring of the AMF phylum Glomeromycota reallocated the species into genera according to molecular analysis. A systematic review of the literature was synthesized to assess the interaction between Pratylenchus spp. and AMF using the new nomenclature. Arbuscular mycorrhizal fungi inoculated plants generally exhibited greater tolerance as demonstrated by increased biomass under Pratylenchus pressure. Species from the order Diversisporales tended to increase Pratylenchus population densities compared to those from the Glomerales. Species from the genera Funneliformis and Glomus had a reductive effect on Pratylenchus population densities. The interaction between AMF and Pratylenchus spp. showed a variation in response as a result of cultivar, crop species and AMF species used. Putative mechanisms involved in these interactions are discussed.